The Use of Hyaluronic Acid in Reducing Postoperative Complications in Minor Oral Surgery: A Review - F. Ahmed, Alomar,; Saud, Alayed, S.; Abdulaziz, Naitah, N.; Abdullah, Alkadhi, A.; Abdulaziz, Alhassoon, H.; Khalid, Alshahrani, S.; Turki, Alshahrani, S.; Khalid, Alaman, A.; Ziyad, Alsultan, M; Almubarak, Ibtisam K.; et al. (International Journal of Innovative Research in Medical Science, 2024)
Aim: Hyaluronic acid (HA) is a major carbohydrate component of the extracellular matrix, and it is distributed widely throughout connective, epithelial tissues, and neural tissues. Since HA is used to promote healing following dental treatments, it has lately gained recognition as an adjuvant treatment for minor oral surgery. This review aims to give practitioners the most recent possible information regarding HA as an adjuvant treatment for minor oral surgery. Method: A literature search of PubMed and Google Scholar for obtaining the relevant studies revealed an initial screening of 54 studies, and after excluding the out-of-scope, the final included studies were 29 studies. Conclusion: Most reviewed studies reported positive associations with the usage of HA in treating AO, edema, pain, and trismus due to its inherent favorable properties. However, the data suggest that HA interferes with bleeding management.